Sucessão empresarial na alienação do estabelecimento empresarial - Barbosa, Pedro Henrique Laranjeira (2012)
This paper have as it main topic the discussion about succession in asset purchase acquisitions with goodwill. It starts with the presentation of the subject within its economic background. After, it shows the definition of succession under the private law theory and its consequences in the market for corporate control. It appears that under the Brazilian law there are two legal doctrines of the institute. The first is established by the Civil Code, taken here as the general successor doctrine. The second, defined by the provisions of the Bankruptcy law is the special successor doctrine. Finally, the work concludes with a critique of both doctrines